Business case complexity and environmental sustainability: Nonlinearity and optimality from an efficiency perspective. (1st January 2022) - Ben Lahouel, Béchir; Taleb, Lotfi; Ben Zaied, Younes; Managi, Shunsuke
Abstract: The question of whether it is possible to "do well by going green" has been debated at length in the literature on environmental sustainability, but no consensus has been reached to date. Building on stakeholder theory in that a firm's environmental sustainability can improve its competitive advantage, this study investigates the impacts of sustainable environmental practices on the competitiveness of 28 international airlines over 2010–2018. First, we use dynamic network data envelopment analysis to estimate airline operational efficiency as a measure of competitiveness. Second, we use a panel smooth transition regression (PSTR) model to test for nonlinearities and regime-switching behaviors between variables. Then, to account for endogeneity bias, we develop and estimate an instrumental variable PSTR (IV-PSTR) model. The empirical results indicate that the relationship between environmental sustainability and competitiveness has an inverted U shape, meaning there is an optimal level of environmental sustainability beyond which competitiveness decreases. Therefore, it is important for airline managers to understand that very high levels of investment in sustainable practices can have more negative effects compared to very little investment. The study concludes by providing implications for theory and practice. Highlights: Airline competitiveness is measured by a dynamic network DEA model. The PSTR model is more flexible and reliable than conventional econometric models. Too much of environmental expenditures could be harmful above a threshold level.